Resistant sources to late blight in tomato - S.S. SOKHI; SURJAN SINGH, HIRDAY PAL SINGH, S. KAUR (Indian Phytopathology, 2002)
Tomato crop is attacked by a large number of diseases of which late blight (Phytophthora infestans (Mont.) de Bary) is the most destructive one. The yield loss caused by this disease has been reported upto 100 per cent under congenial environmental conditions. The pathogen attacks all the aerial parts of the plant including leaves, stems and immature green fruits. Most of the commercial varieties of tomato are susceptible to this disease. However, some of the commercial varieties reported to be resistant at one place were reported to be susceptible at other places. This is attributed to the racial differences to the pathogen. Therefore, the development of resistant varieties to the races prevalent under local conditions is important. In the present studies, the pathogen Phytophthora infestans (Mont.) de Bary was isolated from the infected leaves of the tomato variety Punjab Chuhara and it was maintained and multiplied on tomato leaves of the same variety at 16 Â± 2Â°C with 85 per cent RH. Inoculum was prepared by washing infected leaves with sterilized water and the final volume was prepared in such a way so that the solution contained 10,000 sporangia per ml. This solution was prepared one hour before inoculation for the release of zoospores. The intensity of zoospore was counted by using haemocytometer and maintained at 10,000 zoospores per ml.